Effects of cleaning interval of PV module and pyranometer on PV system performances in tropical climate of Indonesia - Oo Abdul Rosyid; Yogie Probo Sibagariang; Adjat Sudrajat; Ma'arif Hasan; Nelly Malik Lande; Andrianshah Priyadi; Anita Faradilla; Hartadhi; Setya Sunarna; Himsar Ambarita (Results in Engineering)
Photovoltaic (PV) cleaning is crucial to maintain optimal Performance Ratio (PR) in PV systems. PR is a key metric for acceptance tests and operations. This research evaluates four PV modules with different cleaning intervals (1 week, 2 weeks, 4 weeks and no clean) and analyzes PR calculations with variations of pyranometers cleaned and not cleaned in Indonesian climate conditions. Results showed that weekly cleaning minimized output degradation by 1.58 % compared to no cleaning, which led to a 2.37 % decrease. Bird droppings increased PV temperature by 10.2 °C. Accurate PR measurement requires cleaning both PV modules and pyranometers.